R. vesicarius L. exerts nephroprotective effect against cisplatin-induced oxidative stress - Md. Mahmudul Hasan; Most. Sayla Tasmin; Ahmed M. El-Shehawi; Mona M. Elseehy; Md. Abu Reza; Ariful Haque (BMC, 2021)
Abstract Background Cisplatin is an outstanding anticancer drug, but its use has been decreased remarkably due to sever nephrotoxicity. R. vesicarius L. is a leafy vegetable that is evident with anti-angeogenic, anti-inflammatory, anti-proliferative, hepatoprotective, and nephroprotective potential. Therefore, this study was designed to inspect its methanol extract (RVE) for possible nephroprotective effect. Methods Primarily, in vitro antioxidant activity of RVE was confirmed based on 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging aptitude. Thereafter, Swiss Albino male mice were treated with cisplatin (2.5 mg/kg) for 5 successive days to induce nephrotoxicity. Recovery from nephrotoxicity was scrutinized by treating the animals with RVE (25, 50, and 100 mg/kg) intraperitoneally (i.p.) for the next 5 consecutive days. After completion of treatment, mice were sacrificed and kidneys were collected. Part of it was homogenized in sodium phosphate buffer for evaluating malondialdehyde (MDA) level, another part was used to evaluate gene (NQO1, p53, and Bcl-2) expression. Moreover, the hydrogen peroxide (H2O2) neutralizing capacity of RVE was evaluated in HK-2 cells in vitro. Finally, bioactive phytochemicals in RVE were determined using gas chromatography-mass spectrometry (GC-MS). Results RVE showed in vitro antioxidant activity in a dose-dependent fashion with 37.39 ± 1.89 μg/mL IC50 value. Treatment with RVE remarkably (p < 0.05) decreased MDA content in kidney tissue. Besides, the expression of NQO, p53, and Bcl-2 genes was significantly (p < 0.05) mitigated in a dose-dependent manner due to the administration of RVE. RVE significantly (p < 0.05) reversed the H2O2 level in HK-2 cells to almost normal. From GC-MS, ten compounds including three known antioxidants "4H-Pyran-4-one, 2, 3-dihydro-3,5-dihydroxy-6-methyl-", "Hexadecanoic acid", and "Squalene" were detected. The extract was rich with an alkaloid "13-Docosenamide". Conclusion Overall, RVE possesses a protective effect against cisplatin-induced kidney damage.